MATHEMATICAL CONCEPTS IN SCOUTING TECHNICAL ACTIVITIES: A STUDY ON PIONERING BUILDINGS - Nupatihatul Aeni Djibrilu; Imaludin Agus; Muhammad Syarwa Sangila; Amanda La Hadi; Dedyerianto Dedyerianto (Math Educa Journal, 2025)
Mathematics learning in schools is still abstract and not yet relevant to students' lives. Mathematics learning should be linked to student activities such as scouting extracurricular activities. There are many scouting technical activities that can be used as contextualization in mathematics learning such as ceremonies, exploration, estimating, marching, pioneering, and semaphore. Thus, this study aims to identify mathematical concepts contained in scouting activities, especially in the construction of creative flagpole pioneering. This study is a qualitative study with an exploratory approach. Data collection methods used are observation, interviews, and documentation. The study was conducted on students who participate in scouting extracurricular activities at SMAN 2 Kendari, located on Jln. Sisingamangaraja, Rahandouna Village, Poasia District, Kendari City, Southeast Sulawesi Province. The results of the study show that in the pioneering flagpole creation building there are geometric concepts, namely rectangular, square, right triangle, acute triangle, obtuse triangle, right trapezoid, isosceles trapezoid, arbitrary trapezoid, right angle, acute angle, obtuse angle, overlapping lines and intersecting lines. and geometric transformations, namely rotation. These results provide recommendations to teachers to be able to use the pioneering building as an introduction to mathematical concepts.